2018
DOI: 10.1037/pne0000113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intermediate repeated items on immediate recall in a modified Hebb paradigm.

Abstract: Studies that used the Hebb paradigm have contributed to our understanding of the way in which short-term serial information is consolidated in long-term memory. However, it is unclear whether the learning of repeated series occurs solely within a serial context. Therefore, the purpose of this study was to determine whether the repetition of intermediate items in a given list is conducive to learning these items. We modified the Hebb paradigm by introducing repeated stimuli only in midlist positions. Letter lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…In general, errors occur more frequently in the central elements of the sequence. For this reason, Leite et al (2018) carried out four experiments to explore the experimental conditions that promote learning of central elements of a sequence. In a first experiment, they presented 36 lists of 9 consonants each.…”
Section: Efecto De La Contigüidad Espacial Sobre El Aprendizaje De Se...mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, errors occur more frequently in the central elements of the sequence. For this reason, Leite et al (2018) carried out four experiments to explore the experimental conditions that promote learning of central elements of a sequence. In a first experiment, they presented 36 lists of 9 consonants each.…”
Section: Efecto De La Contigüidad Espacial Sobre El Aprendizaje De Se...mentioning
confidence: 99%
“…The facilitating effect of the signal was lost. Research by Leite et al (2018) showed that the implementation of signaling strategies of central positions of a sequence favored its recall. It is a relevant finding since errors mostly occur in central positions.…”
Section: Efecto De La Contigüidad Espacial Sobre El Aprendizaje De Se...mentioning
confidence: 99%